Assessing the Role of Career Development, Work Environment, and Workload in Enhancing Teacher Performance - Krisna Cahyantika; Sutianingsih, Sutianingsih (Cita konsultindo, 2025)
This study aims to analyze the influence of career development, work environment, and workload on teacher performance at SDIT Nur Hidayah. Teacher performance is considered a crucial factor in determining the quality of education, so understanding the factors that affect it is very important. This study uses a quantitative approach with a survey method. The research population is all teachers at SDIT Nur Hidayah which is 68 people, and the sampling technique uses the census method. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 26 software. The results showed that the three independent variables of career development, work environment, and workload partially had a significant and positive influence on teacher performance. In addition, simultaneously, these three variables also have a significant influence on teacher performance.